1976
DOI: 10.1007/bf01471576
|View full text |Cite
|
Sign up to set email alerts
|

Effects of free fatty acids on electrophysiological properties of ventricular myocardium

Abstract: Several metabolic factors have been regarded as a cause of ventricular tachyarrhythmias in cardiac ischemia, i.e. hypoxia, acidosis, intracellular potassium loss, local catecholamine release as well as an increased catecholamine concentration and an evaluation of serum free fatty acids. The arrhythmogenic properties of anoxia and hypoxic acidosis, catecholamines as well as potassium depletion are well known. However, the relationship between elevated free fatty acids concentration and the occurrence of ventric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

1979
1979
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 36 publications
1
1
0
1
Order By: Relevance
“…The action potential shortening observed in the present study mirrors results obtained by others in whole tissue preparations. Palmitate (0.84 or 1.3 mM, complexed to 2% BSA), for example, has been shown to cause action potential shortening in papillary muscle [48]. Similarly, Willebrands and colleagues reported that perfusion of the isolated rat heart with palmitate (1–3 mM, complexed with 0.66 mM BSA) induced arrhythmias and reduced contractility in agreement with the present data [49].…”
Section: Discussionsupporting
confidence: 87%
“…The action potential shortening observed in the present study mirrors results obtained by others in whole tissue preparations. Palmitate (0.84 or 1.3 mM, complexed to 2% BSA), for example, has been shown to cause action potential shortening in papillary muscle [48]. Similarly, Willebrands and colleagues reported that perfusion of the isolated rat heart with palmitate (1–3 mM, complexed with 0.66 mM BSA) induced arrhythmias and reduced contractility in agreement with the present data [49].…”
Section: Discussionsupporting
confidence: 87%
“…das Herz vor einer unnötigen Stoffwechselsteigerung bzw. sonstigen nicht essentiellen Trijodthyroninwirkung schützt und somit das Risiko von Arrhythmien vermindert (KURIEN et al 1971;LÜDERITZ et al 1976;STRANGE et al 1978;LÜDERITZ 1982).…”
Section: Schilddrüsenhormoneunclassified
“…The constituents in plasma are important in regulating cell function and maintaining homeostasis. For example, potassium affects cell excitability and severe depletion will cause muscle weakness and abnormalities of the cardiac impulse (3). To avoid the protein confounding effects of the cellular fractions of the blood on clinical biochemistry tests (1), the tests are often performed on cell-free samples, such as plasma or serum.…”
Section: Introductionmentioning
confidence: 99%